Concentrations of Volatile Organic Compounds (VOCs) at a Former Gasworks - , A. N. Nwachukwu; , R. F. Njoku-Tony; , T. E. Ebe (Archives of Current Research International, 2019)
Former Gasworks are often associated with widespread contaminant source in the subsurface, which produce large plumes that comprise a wide variety of tar-oil related compounds. Whilst most of these compounds undergo degradation naturally, the processes are often slow and inefficient usually taking many decades and often leaving active remediation as the only feasible option to eliminate the risks of toxic substances to reach potential receptors such as ground/surface waters or drinking water wells. In this study we measured and analysed aggregate concentrations of volatile organic compound (VOC) and their individual components at a large town’s Former Gasworks. Measurements were conducted at various boreholes on the site; however, for the purpose of this paper only two boreholes were considered, the one closest to the former retort house (borehole1) and one at some distance from it (borehole 2). The aggregate concentrations of VOCs were obtained using an in-borehole gas monitor called Gasclam whilst a Tenax TA sorbent tube incorporated into and to work in parallel with this instrumentation was used to adsorb bulk concentrations of VOC and subsequently desorbed (for characterisation) using thermal desorption/gas chromatography-mass spectrometry (TD/GC-MS) technique. The result shows VOCs in borehole 1 to exhibit a broader range and have higher average concentrations. The values range from 40 ppm - 230 ppm borehole 1 and 32 ppm - 45 ppm in borehole 2. Whilst the former has average VOC concentration of 166 ppm/hour; the latter has 38 ppm/hour as its average over the monitoring period. Among the identified VOCs are those considered to be hazardous to health such as toluene, chlorobenzene, xylene, ethylbenzene and isopropylbenzene.